Optical Waveguide Interconnects in Optoelectronic Matrix Switches - Ersoni, Michael (My University, 1995)
The speed and simplicity of the metal-semiconductor-metal (MSM) detector has made it a prime candidate for use in integrated optoelectronic circuits. While in most applications the optical input is coupled in through the top surface of the device, it is also possible to distribute the optical signal by means of transparent waveguides that are located below the absorbing detector layer. By controlling the degree of coupling between the waveguide and detector layers the detectors can be made to act as optical taps. The optical signal can thus be shared among a series of detectors as required in optoelectronic switching applications. We have made a series of simple ridge waveguides, each with a number of MSM structures designed for the characterization of absorption, responsivity and frequency response. A 4x4 optoelectronic switch was also fabricated and analyzed. We show that balancing the switch is accomplished by tailoring the absorption coefficient in the detector region so that all detectors absorb equal amounts of optical power.
Keywords: optical waveguide; optoelectronic matric switch